A Modified Design for Posterior Inlay-Retained Fixed Dental Prosthesis - Abdulaziz Samran; Mohammad Zakaria Nassani; Marwan Aswad; Amid Abdulkarim (Case Reports in Dentistry)
The aim of this paper is to report a clinical case with bilateral missing mandibular second premolars that were restored by metal-ceramic inlay-retained fixed dental prostheses. The first prosthesis was of a traditional design and the second was of a modified design. The suggested design is created by modifying the retainer wings of the traditional resin-bonded inlay-retained fixed dental prosthesis and covering the wings with composite resin. The modified design is relatively conservative, esthetic and provides an extra element for the retention of posterior metal-ceramic inlay-retained fixed dental prostheses.